APPLICATION OF STEM CELLS IN TREATMENT OF ORAL LICHEN PLANUS (Journal of Medical & Health Sciences Review, 2025)
Background:Oral lichen planus (OLP) is a chronic inflammatory mucocutaneous disorder of autoimmune origin, often presenting as painful erosive or atrophic lesions in the oral cavity. Conventional therapies such as corticosteroids and immunosuppressants offer temporary relief but are associated with side effects and recurrence. Recent advancements in regenerative medicine highlight mesenchymal stem cells (MSCs), particularly gingiva-derived MSCs (GMSCs), for their immunomodulatory and regenerative potential.Objective:This study aimed to evaluate the safety and clinical efficacy of autologous gingiva-derived mesenchymal stem cells in the management of erosive OLP through a randomized, double-blind, placebo-controlled clinical trial.Methods:A total of 48 patients aged 30–65 years with clinically and histopathologically confirmed erosive OLP were randomized into two groups (n=24 each). The experimental group received three biweekly submucosal injections of GMSCs (1×10⁶ cells/mL), while the control group received placebo saline injections. Pain was assessed using the Visual Analog Scale (VAS), lesion size measured via digital calipers, and lesion severity evaluated using the Thongprasom score. Quality of life was assessed with the OHIP-14 questionnaire, and salivary levels of IL-6 and TNF-α were analyzed using ELISA at baseline, 2, 4, and 12 weeks post-treatment. Safety and adverse events were also monitored.Results:The MSC group demonstrated significant reductions in pain (VAS: from 6.9 to 1.0), lesion size (from 86.5 mm² to 20.7 mm²), and Thongprasom score (from 4.3 to 0.8) by week 12 (p